MLH1 and MSH2 Gene Mutations and Polymorphisms in Six Malay Families with Hereditary Nonpolyposis Colorectal Cancer - Wan Juhari, Wan Khairunnisa; Amin Noordin, Khairul Bariah Ahmad; Wan Abdul Rahman, Wan Faiziah; Zakaria, Andee Dzulkarnaen; Mohd Sidek, Ahmad Shanwani; Abu Hassan, Muhammad Radzi; Macrae, Finlay; Zilfalil, Bin Alwi (IIUM Medical Journal Malaysia, 2018)
Background: Hereditary nonpolyposis colorectal cancer (HNPCC) also known as Lynch syndrome is commonly caused by genetic alterations in any of the four mismatch repair (MMR) genes; MLH1, MSH2, MSH6 and PMS2. This is the first study aimed to investigate genetic variants in Malay HNPCC families. Methods: Six Malay HNPCC families who fulfilled any of the Bethesda criteria were recruited into this study. A total of 3 ml of blood was withdrawn from each patient in the families. The samples were further analyzed using polymerase chain reaction and direct sequencing of the selected exons of MLH1 and MSH2 genes. Results: Two missense mutations and four single nucleotide polymorphisms (SNPs) were identified in six patients. These variants in the MLH1 and MSH2 genes were identified in four families who met the revised Bethesda guidelines. In two families, no mutation and polymorphism was identified in both the exon and intron of the respective genes. Of the mutations and polymorphisms identified, five have never been reported in Malay HNPCC families before. A missense mutation was detected in exon 5 of the MLH1 gene, c.394G>C (p.Asp132His) and four mutations and polymorphisms were detected in the MSH2 gene; heterozygous c.211+98T>C and c.211+9C>G and homozygous c.211+98T>C and c.211+9C>G, c.367-86A>C and c.382C>G. Conclusion: The results represented a new spectrum of mutations and polymorphisms in the Malay HNPCC families. However, a larger study involving additional families and analysis is required to determine the impact and nature of the identified mutations and polymorphisms.